2020
DOI: 10.1002/ppul.25191
|View full text |Cite
|
Sign up to set email alerts
|

High frequency percussive ventilation in pediatric acute respiratory failure

Abstract: Objective: High frequency percussive ventilation (HFPV) is used in acute respiratory failure, but is poorly described in pediatrics. We aimed to describe the clinical characteristics, ventilator settings, and outcomes of a large pediatric cohort, and to determine predictors of who would benefit from HFPV. Hypothesis: Gas exchange 2 h after HFPV initiation predicts success. Design: Single center retrospective cohort study testing association between gas exchange 2 h after HFPV initiation with success, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…HFPV has been in use for over 30 years, and though its use has not been adopted widely, it has been shown to improve gas exchange in a variety of adult and pediatric populations ranging from those with respiratory failure postcardiac surgery to inhalation injury. 3,4,6,7,[16][17][18] Our data suggest HFPV has efficacy in ventilating patients with bronchiolitis, with a mean drop in P CO 2 of 14 mm Hg in the 24 h post-HFPV initiation. Studies by Rizkalla, 3 respiratory failure and also illustrated improved ventilation, with P CO 2 analyzed in their studies at 24, 6, and 2 h post-HFPV, respectively.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…HFPV has been in use for over 30 years, and though its use has not been adopted widely, it has been shown to improve gas exchange in a variety of adult and pediatric populations ranging from those with respiratory failure postcardiac surgery to inhalation injury. 3,4,6,7,[16][17][18] Our data suggest HFPV has efficacy in ventilating patients with bronchiolitis, with a mean drop in P CO 2 of 14 mm Hg in the 24 h post-HFPV initiation. Studies by Rizkalla, 3 respiratory failure and also illustrated improved ventilation, with P CO 2 analyzed in their studies at 24, 6, and 2 h post-HFPV, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…15 Though our data suggest a potentially decreased risk of barotrauma from HFPV including no cases of air leak secondary to HFPV, other studies confirm that HFPV can be associated with those findings. Butler et al 7 reported an 8% (18/237) incidence of air leak post-HFPV, and Rizkalla 3 and Tawfik 6 each reported one case in their cohorts (3% and 4%, respectively). Our finding that HFPV does not produce hemodynamic instability in bronchiolitis is supported by similar findings in studies by Oribabor et al 25 in adult cardiac subjects and by Rizkalla et al 3 and Butler et al 7 in children with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the setting of acute hypoxic respiratory failure, HFOV has not been shown to reduce mortality in adult or pediatric patients. Currently, there are insufficient data to recommend other forms of alternative ventilation like high-frequency HFPV, HFJV, or APRV [13][14][15]. The PEMVECC consensus recommendations did caution use of HFJV in patients with obstructive airway disease secondary to the risk of dynamic hyperinflation.…”
mentioning
confidence: 99%